Digital supply networks : transform your supply chain and gain competitive advantage with disruptive technology and reimagined processes - Sinha, Amit, 1980-; Bernardes, Ednilson; Calderon, Rafael (McGraw-Hill, 2020)
"Digital transformation has changed the way we live and work. The rapid evolution of digital technologies is fundamentally transforming supply chain management processes. Competitive success now depends on the strategic adoption of new technologies and the digitalization of demand-supply systems, more collaborative and connected processes, and smarter, more dynamic data-driven decision making-a fully integrated "Digital Supply Network." Digital Supply Network examines the impact new technology has had on supply chain management processes, sub-processes, technologies, and best practices. Drawn from real world-experience and stellar academic research, the book provides an in-depth account of the move to digitally connected supply chain management networks. Filled with expert insights and real-life case studies, this is an essential guide to fully integrating digital supply networks for maximum competitive advantage. You'll learn everything you need to know about: How DSN redefines the principles of SCM for the digital eraPhases, roles, technology, and the benefits of DSNData quality, lifecycle, security, authority, and analytics Practical application of technologies like Machine Learning, Artificial Intelligence, Blockchain, Robotics and Additive Manufacturing, and the Internet of Things (IoT)Synchronized planning, demand forecasting, and responsive supply planningManagerial aspects of digital technologies, and approaches for evaluation and useHarnessing demand-supply-logistics technology for greater organizational successDigital product development, and more"--